New Development Bank as Aid Donor to School Education - Rodion Sadykov; Yevgeny Uchaev (Vestnik MGIMO-Universiteta)
Despite initial expectations that the New Development Bank (NDB) would emerge as a significant contributor to education aid, educational projects constitute only 0.3% of the Bank’s portfolio after nine years of operation. Why have the aspirations of the mid-2010s remained largely unrealized? Drawing on primary sources, including official BRICS and NDB documents, speeches by member states’ representatives, and aid statistics, this article traces the evolution of education aid within the NDB’s operational framework. The analysis tests several hypotheses to explain this trajectory, examining BRICS member states’ preferences for educational cooperation, leadership changes within the Bank, the impact of COVID-19, the demand for educational aid among NDB member states, and the division of labor between “old” and “new” multilateral development banks.The findings indicate that the inclusion of education as a secondary focus area in the NDB’s agenda initially exemplified a case of “governing through goals,” as the Bank sought to enhance its reputation by contributing to the broadest possible range of Sustainable Development Goals (SDGs). Subsequent developments, including heightened attention to BRICS educational cooperation at high-level and ministerial meetings, the adverse impact of COVID-19 on global educational progress, and the appointment of Dilma Rousseff as NDB President, further solidified social infrastructure (including education) as a priority on the Bank’s strategic agenda. However, despite increased rhetorical emphasis in declarations and strategic documents, financing for educational projects has not followed suit.This disconnect can be attributed to two primary factors. First, the established division of labor between “old” multilateral development banks (e.g., World Bank, Inter-American Development Bank, Asian Development Bank) and “new” institutions (e.g., NDB, AIIB) has positioned the former to prioritize social sector investments while the latter address deficits in infrastructure financing. Second, NDB member states have shown limited interest in altering this status quo. At the same time, stagnating aid volumes and the increasing politicization of educational aid by traditional donors, coupled with persistent needs to improve education systems in many developing countries, underscore the challenge for BRICS states to develop more effective mechanisms for educational cooperation—both within the bloc and with the broader Global South.